Optical Fibers and Their Applications 2014 - Dorosz, Jan; Romaniuk, Ryszard S. (Photonics Letters of Poland, 2014)
Conference Series on Optical Fibers and Their Applications held its 15th edition in Białystok and Lipowy Most in the end of January 2014. The paper is a concise digest of work results presented there from the main domestic laboratories active in optical fiber and planar photonics. Conference topics were: optical fiber technology, materials for optoelectronics and photonics, rare earth doped and luminescent materials, metrology of optical fibers, components and optoelectronic circuits, applications of optical fibers, waveguides and optical fiber sensors, and lighting technology. Full version of the OFTA2014 digest paper was published in [1]. Proceedings of previous OFTA conferences were published in [2, 3]. Full Text: PDF References R.S.Romaniuk, J.Dorosz, (Edit.)"Development of optical fiber technology in Poland: 2014", Optical Fibers and Their Applications 2014, Proc.SPIE 9228, May 2014 CrossRef J.Dorosz, R.S.Romaniuk (Edit.),"Front Matter: Volume 8010", Optical Fibers and Their Applications 2011, Proc.SPIE 8010, CrossRef R.S.Romaniuk, W.Wójcik (Edit.), "Front Matter: Volume OA100", Optical Fibers and Their Applications 2012, Proc.SPIE 8698, CrossRef Central Office of Measures DirectLink Space Research Centre, Polish Academy of Sciences DirectLink